Modalities of Daughters in Patriarchal Traditions in the Batak Tribe Society - Tamara Damai Yanti Sianturi; Achmad Hidir (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
Batak society is a traditional society that adheres to a patriarchal system that places men as power holders and dominates roles in the group system. In Batak culture, the highest decision is in the hands of men, so there are differences in values between girls and boys. Child modality can be defined as the way of parents in modality, namely supporting, sustaining and being the basis for a child to develop in his life. The purpose of this research is to find out how the modality of girls in Batak society is. The subjects of this study were 6 people who were members of the United Batak Youth PAC Bathin Solapan. The method used is qualitative with the technique of determining informants using a purposive sampling technique. The theory used is the modality theory of Pierre Bourdieu with data collection techniques using interview and observation techniques. Based on the results of the research, the modality for girls is implemented well, even though the presence of patriarchal traditions in Batak society does not prevent the informants from giving the best for their daughters.